2008
DOI: 10.1002/ls.57
|View full text |Cite
|
Sign up to set email alerts
|

Low‐ and zero‐sulphated ash, phosphorus and sulphur anti‐wear additives for engine oils

Abstract: Modern engine lubricant specifications include compositional constraints in terms of the permitted level of sulphated ash, phosphorus and sulphur (SAPS). This necessitates a reduction in the concentration of the additive zinc dialkyldithiophosphate (ZDDP) used in engine oils, and there is currently great interest in identifying anti‐wear additives that contain low or zero SAPS to partially or wholly replace ZDDP.This paper reviews the main chemical classes that are reported in the literature as potential low‐ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
133
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(137 citation statements)
references
References 149 publications
2
133
0
2
Order By: Relevance
“…Similar findings with engine oil on metal surfaces have been reported to contain films composed of low concentrations of Zn, P, S with Ca and O as the topmost layer of the tribofilm [15]. These species have been reported to affect the antiwear properties of tribofilms [22,23]. Uy et al [24] also investigated the tribofilms formed on tappets with Raman and observed Ca/Zn orthophosphate (Zn 3 (PO4) 2 ), CaCO 3 , Fe 3 O 4 with some undecomposed hydrocarbon on the surface.…”
Section: Introductionsupporting
confidence: 75%
“…Similar findings with engine oil on metal surfaces have been reported to contain films composed of low concentrations of Zn, P, S with Ca and O as the topmost layer of the tribofilm [15]. These species have been reported to affect the antiwear properties of tribofilms [22,23]. Uy et al [24] also investigated the tribofilms formed on tappets with Raman and observed Ca/Zn orthophosphate (Zn 3 (PO4) 2 ), CaCO 3 , Fe 3 O 4 with some undecomposed hydrocarbon on the surface.…”
Section: Introductionsupporting
confidence: 75%
“…In order to control pollution, European and American countries have enacted stringent new emission standards that require an extended life for exhaust systems, improved fuel efficiency, and the use of less toxic biodegradable lubricants with acceptable environmental compatibility. The new specified limits of sulfated ash, phosphorous, and sulfur in lubricants are lower than previously defined ones [1]. These limits now require adjusting and improving engine oil formulations, the gradual introduction of ash-less antioxidants, anti-wear additives, and enhancements in dispersant and viscosity indices.…”
Section: Introductionmentioning
confidence: 88%
“…2 An alternative approach to replacing ZDDP by other anti-wear additives is to remove the need for an anti-wear additive in the fi rst place, and one possible way to do this is to coat the surfaces of rubbing engine components with highly wear-resistant materials. One very promising material is diamond-like carbon (DLC), and the third paper describes work on a particular type of DLC coating and its very effective interaction with the unusual friction-reducing agent, glycerol.…”
Section: Beyond Zddpmentioning
confidence: 99%